The influence of work discipline and work motivation on the performance of employees of disduk capil of disduk capil Tangerang Regency - Tamara Nurfadillah; Herayati Herayati; Martinus Wahyu Purnomo (Trigin Publisher, 2023)
Based on the results of temporary observations in the field, it appears that there are several problems related to employee performance. In terms of Work Discipline and in terms of work motivation. If this is left unchecked and does not get attention, it will have an impact on the performance of the Tangerang Regency Population and Civil Registration Office employees. This study aims to determine whether work discipline and work motivation simultaneously or partially affect the performance of employees of the Tangerang Regency Population and Civil Registration Office. The sample of this research is 38 respondents. The data analysis technique used is the multiple linear regression equation. The results of the study show that work discipline and work motivation have a significant simultaneous effect on employee performance at the Department of Population and Civil Registration of Tangerang Regency. calculated F value of 19,487 > F table 3.27, with a sig value of 0.00 <0.05. Work Discipline partially has a significant effect on employee performance at the Department of Population and Civil Registration of Tangerang Regency. with a calculated t value of 2.139 > t table of 2.0301, with a sig value of 0.039 <0.05 and work motivation partially has a significant effect on the performance of the Tangerang Regency Population and Civil Registration Service Employees. with a calculated t value of 3.475 > t table of 2.0301, with a sig value of 0.001 <0.05.